KUALITAS PELAYANAN PADA OPERASIONAL ROOM SERVICE HOTEL NOVOTEL PEKANBARU - Yosi Suwarni; Teguh Widodo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Restaurant is a building that provides food and drink. Especially in a hotel, restaurant is one of the part that adds a lot of hotel revenue. The research was conducted in All Day Dining Restaurant (Food Exchange)Novotel Hotel Pekanbaru. This hotel is chosen as a place of research because they have high occupancy and they have high user room service. This study aims to find out how the quality of service room service operations Novotel Hotel Pekanbaru. This research uses qualitative descriptive method which is researches tried to describe the real situation by collecting information and explain in detail way or make a prediction before. Data collection technique are used with observation, interview and documentation. The observation target of this researce are supervisor, captain and three of waiters. Based on research that has been done about quality of service then obtained at the operational room service is good and must be maintained or improved. Keywords: quality, service, room service